ANALISIS KAIDAH URF PADA FATWA DSN – MUI NO 54 TENTANG SYARIAH CARD - RIZAL, RIZALUDDIN; HAFIDHUDDIN, DIDIN; AYUNIYYAH, QURROH (Universitas Ibn Khaldun Bogor, 2023)
Humans are social beings who rely on interactions with others to meet their daily needs. Economic activities, such as buying and selling transactions, have evolved over time. Initially, transactions were done through bartering, but the introduction of money made transactions easier. The world of economics and banking is constantly evolving, resulting in innovations like the sharia card. This product was created to meet the community's need for a credit card that complies with sharia principles. The Indonesian Ulema Council issued fatwa No. 54, which addresses the sharia card and references the fiqh rule on urf. This research examines the relationship between the emergence of sharia card products and urf evidence. It aims to determine if the needs of the sharia economic community in Indonesia have reached the urf level. The study also explores the sharia card agreement outlined in fatwa No. 54. Through qualitative research based on library sources, it was found that the community's needs have not yet reached the level of urf, but rather a level where credit card use is common. However, this does not invalidate the fatwa, as it includes other arguments and rules to uphold sharia principles. This research serves as an example for studying fatwa sheets issued by DSN-MUI, providing additional knowledge for those interested in the topic. It sheds light on the development of sharia-compliant financial products and their relevance in the contemporary economic landscape.